2003
DOI: 10.1021/om020778o
|View full text |Cite
|
Sign up to set email alerts
|

One-Electron Oxidation of Heterodinuclear Organometallic Compounds Having Polyphosphido Bridges

Abstract: The electrochemical behavior of several heterometallic compounds having polyphosphido bridges has been investigated. Reversible one-electron oxidations were observed for Cp*Fe-(P 5)TaCp′′ (2), Cp*Fe(P 5)[Ir 2 (CO) 2 Cp* 2 ] (3), and Cp′′′ 2 Co 2 (P 2) 2 (4) (Cp*) C 5 M 5 , Cp′′) C 5 H 3 t Bu 2 , Cp′′′) C 5 H 2 t Bu 3). In contrast to the pseudo-sandwich polyphosphido complex Cp*FeP 5 (1), compounds 2-4 undergo very facile oxidations and the corresponding monocations may be generated by bulk electrolysis or by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It is shown that 2 , 3 , 6 , and 7 each display one quasi-reversible reduction process, one irreversible reduction process, and one irreversible oxidation process. All the first quasi-reversible reductions ( E pc = −1.62 to −1.64 V) are one-electron processes, which is supported by the calculated value of 0.9 faraday/equiv (obtained through study of bulk electrolysis of 7 ) and the calculated value of ( i p /ν 1/2 )/( it 1/2 ) = 4.08 (obtained through study of CV and chronoamperometry (CA) of 7 ) . These one-electron processes can be assigned to the reduction of Fe I Fe I to Fe I Fe 0 .…”
Section: Resultssupporting
confidence: 60%
“…It is shown that 2 , 3 , 6 , and 7 each display one quasi-reversible reduction process, one irreversible reduction process, and one irreversible oxidation process. All the first quasi-reversible reductions ( E pc = −1.62 to −1.64 V) are one-electron processes, which is supported by the calculated value of 0.9 faraday/equiv (obtained through study of bulk electrolysis of 7 ) and the calculated value of ( i p /ν 1/2 )/( it 1/2 ) = 4.08 (obtained through study of CV and chronoamperometry (CA) of 7 ) . These one-electron processes can be assigned to the reduction of Fe I Fe I to Fe I Fe 0 .…”
Section: Resultssupporting
confidence: 60%
“…Therefore, the formation of an acyclic P 4 bridge among the three metals in 1a and 1b was initiated by the transfer of one electron from the samarocene to [(Cp‴Co) 2 (μ,η 2:2 -P 2 ) 2 ]. Even though Winter and Geiger examined the quasi-reversible one-electron oxidation process of [{Cp‴Co(μ,η 2:2 -P 2 )} 2 ] to [{Cp‴Co(P 2 )} 2 ] + ( E 0 1/2 = 0.33 V) by cyclic voltammetry, one-electron reduction of this dicobalt μ,η 2:2 -polyphosphide complex has not been reported. For this reason, we performed cyclic voltammetry studies of the one-electron reduction process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…: 2.737 and 2.705 Å). Compound [{(η 5 -C 5 H 5 )Co-(μ,η 2:2 -P 2 )} 2 ] 9 can be formally considered as a complex in which two P 2 2− ligands bridge two [(η 5 -C 5 H 5 )Co III ] 2+ cations.Geiger et al22 have shown that the analogue complex [{(η 5 -C 5 H 2 t Bu 3 )Co(μ,η 2:2 -P 2 )} 2 ] undergoes reversible oxidation to the monocation at E 1/2 = −0.33 V and a partially reversible oxidation to the dication at E 1/2 = 0.33 V. Geometry optimization of the dication 9 2+ (see Fig.12, right side) leads to a triple decker sandwich complex with a regular cyclo-P4 ligand (P-P bond distances: 2.316 Å, Co-P bond distances: 2.378 Å) in the middle deck. The central Co 2 P 4 unit may also be considered as a heteroatom substituted octahedral cluster with cyclopentadienyl ligands coordinating the cobalt atoms.…”
mentioning
confidence: 99%